(untitled) (Journal of Engineering, 2005)
The present work deals with an experimental investigation of the effect of surfacing parameters on the final quality of large gear surfacing. This gear forms a vital part of the drive train of cement furnace at the Iraqi Cement Company. The gear is made of DIN CK 45 steel with an analyzed carbon content of 0.429% and core hardness 185 HV. The gear is considered large, with dimensions of 490 mm in diameter, 250-mm width and 27 mm module, its weight is 350 Kg. The aim of the present work is to study the possibility of repairing this type of gear using SMAW process. The gear surface is cleaned by sand blasting, followed by dye penetrate testing for crack detections. DIN E1-UM350 hardfacing electrode is selected to hardface the gear. This electrode has a nominal composition (0.08% C, 3.3%Cr, 1%Mn) and a minimum hardness 350 HV. The gear teeth are surfaced with one, two, and three layers with and without preheating. The preheating temperature is 200 C°, which is, selected according to carbon equivalent of the DIN CK 45 base metal. Cracks were observed in the weld metals when surfacing with three layers of El-UM350 electrode. So, E 8018-B2, and E 9018-D, are selected to butter the gear surface with one layer, followed by two layers of El-UM350 electrode. These low hydrogen electrodes are selected based on their mechanical properties compared with DIN CK 45 base metal and low hydrogen content which eliminate hydrogen induced cold cracking. Preheating the gear surface gives good hardness distribution across the weld, HAZ, and base metals due to reducing the cooling rates and prevents hard structure to form at the interface region. A set of destructive and non destructive tests are carried out. Including, tensile, wear, impact, chemical analysis, metallographic, micro hardness, macro etchent, and dye penetrate tests. Both of wear and impact resistance of all specimens is greater than the base metal. All weld deposits of El- UM350 hardfucing electrode gives martensitic structures with different hardnesses depending on the cooling rates and number of layers. Using of low hydrogen electrodes (E 8018-B, and E 9018-D) as buttering layers, solve the cracking problem of weld deposits when surfacing with three layers of El-UM350 electrodes